MEDICAL MANAGEMENT OF UTERINE TORSION AND ADHESIONS COMPLICATING DYSTOCIA IN A HOLSTEIN FRIESIAN CROSSBRED COW - Williams, V; Roberts, S; Nanda, M (International Journal of Allied Sciences (IJAS), 2022)
Uterine torsion is a rare but challenging condition in dairy cows that can result in dystocia and even death. This report presents a case of uterine torsion in a full-term pregnant Holstein Friesian crossbred cow that was complicated by uterine adhesions. The cow was referred to a Large Animal Obstetrical Unit after unsuccessful treatment by a local veterinarian for symptoms including restlessness, inappetence, abdominal discomfort, and frequent lying down and getting up. Vaginal and rectal examinations revealed right side pre-cervical uterine torsion and adhesion of the uterus with adjacent organs. Due to the delayed condition and development of uterine adhesions, a caesarean section was performed as per the standard procedure. A dead male fetus and fetal membranes were removed during the surgery, and the adhesion of the uterus was corrected manually. The animal was treated postoperatively with antibiotics, anti-inflammatories, antihistamines, ecbolics, and IV fluids for seven days and had an uneventful recovery. The case highlights the importance of prompt diagnosis and treatment of uterine torsion, particularly in cases complicated by adhesions. Caesarean section can be a viable option in such cases.